2010
DOI: 10.1111/j.1432-2277.2010.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous perfusion of donor hearts with oxygenated blood cardioplegia improves graft function

Abstract: Summary Donor hearts cannot be preserved beyond 6 h using cold storage (CS). Improving preservation methods may permit prolonged storage of donor heart. We compared graft function in large animal model after prolonged preservation (8 h) using continuous perfusion (CP) and CS method. Twenty‐four miniature pigs were used as donors and recipients. Donor hearts were either stored in University of Wisconsin solution (UW solution) for 8 h at 0–4 °C (CS group, n = 6) or were continuously perfused with oxygenated bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Findings of decreased oxidative and myocardial injury markers, improved microvascular function and superior myocardial ultrastructure highlight the advantages of continuous normothermic perfusion. 24,[30][31][32] Currently as the only commercially available mobile cardiac perfusion device, the Organ Care System aims to reduce cold ischemia time, minimize myocardial dysfunction, and diminish constraints of procurement distances, thereby optimizing donor utilizations and geographic usage variabilities. Its initial evaluation in the PROCEED II trial assessed clinical outcomes of the Organ Care System compared with standard cold storage, and demonstrated 30-day mortality rates comparable to those of standard cold storage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of decreased oxidative and myocardial injury markers, improved microvascular function and superior myocardial ultrastructure highlight the advantages of continuous normothermic perfusion. 24,[30][31][32] Currently as the only commercially available mobile cardiac perfusion device, the Organ Care System aims to reduce cold ischemia time, minimize myocardial dysfunction, and diminish constraints of procurement distances, thereby optimizing donor utilizations and geographic usage variabilities. Its initial evaluation in the PROCEED II trial assessed clinical outcomes of the Organ Care System compared with standard cold storage, and demonstrated 30-day mortality rates comparable to those of standard cold storage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…At least two previously published reperfusion experiments suggest that this weight increase is not necessarily associated with worse reperfusion cardiac function in organs that maintain satisfactory indices of oxidative metabolism. 19,20 This may be because, as Amirhamzeh et al have suggested, hydrostatic edema resolves when systolic forces return interstitial fluid to the intravascular space after reperfusion, 19 as long as endothelial integrity is maintained. Our own experience in a large animal model of machine perfusion preservation over shorter intervals also demonstrated that despite significant weight gain during the storage interval, myocardial function after implantation was not affected and myocardial water content after reperfusion was not increased.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Hearts in the current study were reperfused for 60 minutes before weaning from CPB, which may have facilitated this process. Outcomes might have been different had we used a shorter reperfusion period.…”
Section: Discussionmentioning
confidence: 99%